AN INVESTIGATION OF THE STUDIES ON DYSCALCULIA IN TURKEY - Baldemir, Bilal; Tutak, Tayfun (My University, 2022)
This study aimed at investigating the studies on dyscalculia in Turkey. For this purpose, document analysis method was used and education and psychology databases were reviewed using the keywords related to \"Dyscalculia-Math Learning Disability\". As a result, 28 studies on dyscalculia were identified and systematically analyzed using content analysis. These studies were analyzed in terms of the year of publication, the university where the thesis or dissertations were conducted, and the journal in which the articles were published. In addition, these studies were analyzed in detail in terms of content and the tools used in the diagnosis of dyscalculia and the strategies for dyscalculic students were presented. Finally, based on the findings of the present study, some recommendations were put forward regarding dyscalculia. Moreover, it is thought that the different methods and techniques, the dyscalculia screening tests and especially the strategies for the treatment of dyscalculia used in the studies will present suggestions for the solution of existing problems and examples that can form a model in the education of dyscalculic students. For this reason, carrying out such systematic analyses on dyscalculia is extremely important for the education of dyscalculic students, as well as being a guide for researchers in this field
Keywords: Eğitim; Eğitim Araştırmaları